CSC248 - Fundementals of Data Strucutures / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
This course provides the concept of information organization and manipulation in a computer to emphasize the use of the data structure in problem solving. An object-oriented approach will be used to develop the programming solutions.